LIVING WITH UNCERTAINTY: GENERALIZED ANXIETY DISORDER AND PSYCHOSOCIAL STRESSORS DURING THE COVID-19 PANDEMIC - Martyna Susek,; Amadeusz Furmanek, (International Journal of Innovative Technologies in Social Science, 2026)
Background: The COVID-19 pandemic created an unprecedented global environment of uncertainty, acting as a profound catalyst for Generalized Anxiety Disorder (GAD). This crisis fundamentally shifted the psychological landscape, revealing that the primary driver of distress was not merely the biological threat of the virus, but a pervasive "certainty deficit" that overwhelmed both individual and systemic coping mechanisms.Methods: This narrative review synthesizes seminal cognitive models of anxiety with contemporary empirical evidence to examine how pandemic-related psychosocial stressors and intolerance of uncertainty (IU) influenced GAD trajectories. A systematic search was conducted across major academic databases, integrating classical theoretical frameworks with peer-reviewed articles and institutional reports published between 2020 and 2026, with a specific focus on the Polish clinical landscape.Results: The synthesis reveals that IU acted as the primary cognitive mediator of anxiety, frequently outweighing the direct fear of viral infection. Social isolation, economic instability, and digital overload, manifested as "doomscrolling," were identified as critical triggers for pathological worry. In Poland, young adults and healthcare workers exhibited the highest vulnerability, with symptoms persisting well into the post-pandemic era. This "long-tail" effect of anxiety is further complicated by secondary behavioral shifts, including documented increases in maladaptive coping strategies such as altered substance use patterns and social withdrawal.Conclusions: Addressing the persistent "mental health debt" requires a paradigm shift in clinical practice. Future interventions must prioritize uncertainty tolerance training and the permanent integration of resilient, digitally-enabled health solutions to ensure a robust safety net for vulnerable populations in the face of future global crises.